CVD (Chemical Vapor Deposition) coating microporous wire-drawing die for hard alloy
By adopting a multi-layer CVD coating structure on the microporous wire drawing die, the problem of insufficient coating bonding force and thermal shock resistance in the prior art is solved, and the high stability and durability of the mold are achieved, and the production cost is reduced. Meets the needs of high-precision processing.
Patent Information
- Application Number
- CN202411561651.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing microporous wire drawing die CVD coatings have shortcomings in terms of binding force and thermal shock resistance, and the production cost is high, making it difficult to meet the needs of high-precision processing.
Using WC-8%Co carbide as the microporous wire drawing die substrate, SiC-TaC layer, BN layer, alumina coating and TiaBb coating are deposited successively through CVD technology to form a multi-layer coating structure to improve the stability of the mold Sex and durability.
It significantly improves the stability and durability of the microporous wire drawing die, enhances the bonding force between the coating and the substrate and thermal shock resistance, reduces production costs, and meets the needs of high-precision processing.
Smart Images

Figure BDA0005118043830000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of CVD coatings for microporous wire drawing dies, in particular to a CVD coating microporous wire drawing die for cemented carbide. Background Art
[0002] Microporous wire drawing dies are key tools in the drawing process of metal wires and wires, and their performance directly affects the quality and production efficiency of the products. In order to improve the stability and durability of microporous wire drawing dies, the industry continues to explore and apply various surface coating technologies. Among them, chemical vapor deposition (CVD) technology has attracted much attention due to its unique advantages.
[0003] CVD technology is a method that converts gaseous substances into solid substances through chemical reactions under specific conditions and deposits them on the surface of the substrate. Specifically, CVD coating can significantly increase the hardness of the wire drawing die, enabling it to withstand higher drawing forces and reduce the wear of the die during use. At the same time, the coating can also protect the base material from corrosion and wear, further extending the service life of the wire drawing die. In addition, CVD coating can also improve the surface quality of the drawn product and meet the needs of high-precision processing.
[0004] However, although CVD technology has made significant progress in microporous wire drawing die coating, there are still some challenges. For example, how to further improve the bonding strength and thermal shock resistance of the coating, and how to optimize the deposition process of the coating to reduce production costs. Therefore, the industry is still constantly exploring and innovating to promote the continuous development of microporous wire drawing die CVD coating technology. Summary of the invention
[0005] The object of the present invention is to provide a CVD coated microporous wire drawing die for cemented carbide to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A CVD coated microporous wire drawing die for cemented carbide, wherein the microporous wire drawing die substrate is made of WC-8% Co cemented carbide, and the CVD coating is SiC-TaC layer / BN layer / aluminum oxide coating / Ti from the surface of the microporous wire drawing die substrate to the outside. a B b coating.
[0008] As an optimization, the total thickness of the CVD coating is 10-20 μm, wherein SiC-TaC layer (2-6 μm) / BN layer (3-5 μm) / aluminum oxide coating (2-4 μm) / Ti a B b Coating (3-5 μm).
[0009] As an optimization, the SiC-TaC layer is prepared by a chemical vapor deposition method. First, SiC is deposited at a deposition temperature of 1200-1300°C, a deposition pressure of 900-1100Pa, a reaction system of trichloromethylsilane / hydrogen / argon, a total deposition time of 7h, and a total of three stages. The deposition time of the first stage is 3h, and the hydrogen / trichloromethylsilane is 2; the deposition time of the second stage is 2h, and the hydrogen / trichloromethylsilane is 3; the deposition time of the third stage is 2h, and the hydrogen / trichloromethylsilane is 4; after the SiC deposition is completed, the TaC layer is deposited at a deposition temperature of 1200-1400°C, a deposition pressure of 4500-5500Pa, the reaction system is tantalum pentachloride / propylene / hydrogen / argon, and the deposition time is 6h.
[0010] As an optimization, the purity of the tantalum pentachloride is greater than 99.95%.
[0011] As an optimization, the feed rate of tantalum pentachloride is 280 r / min.
[0012] As an optimization, the hydrogen / propylene ratio is 7.5
[0013] As an optimization, the BN layer is prepared by chemical vapor deposition, the deposition temperature is 600-700°C, the reaction pressure is 4000-5000Pa, the deposition time is 2h, the reaction system is boron trichloride / ammonia / nitrogen / hydrogen / argon, and the boron trichloride / ammonia / nitrogen / hydrogen is 1:3:6:1.
[0014] As an optimization, the aluminum oxide layer is prepared by chemical vapor deposition, the deposition temperature is 1000-1100° C., the deposition pressure is 30-40 kPa, and the reaction gas is gaseous aluminum halide.
[0015] As an optimization, the Ti a B b The coating is prepared by chemical vapor deposition method, the deposition temperature is 700-900° C., the preparation pressure is 3000-5000 Pa, BCl3 is used as the boron source of the coating, TiCl4 is used as the titanium source of the coating, and H2 is used as the carrier gas.
[0016] As an optimization, the ratio of BCl3, TiCl4 and H2 is 1:4:5.
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] This application adopts an innovative method for constructing the surface coating of a microporous wire drawing die, which is based on chemical vapor deposition (CVD) technology and significantly improves the stability and durability of the die through the careful design of multi-layer coatings.
[0019] First, two layers of specific composite coatings are deposited on the surface of the mold. The inner layer is a SiC-TaC layer, which is in direct contact with the microporous wire drawing die substrate, aiming to enhance the bonding strength between the coating and the substrate, effectively isolate the external environment, and improve the substrate's anti-oxidation performance. This layer utilizes the structural characteristics of SiC and TaC, and through the designability of the CVD process, forms a gradient, multi-layer composite structure, showing excellent mechanical matching and thermal shock resistance.
[0020] Next, the second layer is the BN layer, which mainly plays a role in improving the overall toughness of the coating and strengthening the connection between the inner and outer layers. BN has a layered structure, with atoms in the layers tightly arranged and the layers bonded by weak van der Waals forces. This property enables it to effectively alleviate the mechanical effects caused by the movement of the outer layer. In addition, BN also has excellent oxidation resistance, high-temperature insulation performance, thermal shock resistance and chemical stability, and is chemically inert to molten metal, further improving the overall performance of the coating.
[0021] Subsequently, an aluminum oxide coating and a Ti a B b As the third layer. This layer is designed to improve the bonding strength of the membrane-substrate interface and reduce the cracks between coatings caused by mismatched physical properties (such as thermal expansion coefficient and elastic modulus). By regulating the content of the two phases in the composite coating, the bonding strength of the membrane-substrate interface can be optimized in a large range.
[0022] In summary, the present application achieves comprehensive protection of the surface of the microporous wire drawing die through a carefully designed multi-layer coating structure, significantly improving the stability and durability of the die during use. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0026] The SiC-TaC layer (2 μm) was prepared by chemical vapor deposition. First, SiC was deposited at a deposition temperature of 1200° C. and a deposition pressure of 900 Pa. The reaction system was trichloromethylsilane / hydrogen / argon. The total deposition time was 7 h, which was divided into three stages. The deposition time of the first stage was 3 h, and the hydrogen / trichloromethylsilane ratio was 2. The deposition time of the second stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 3. The deposition time of the third stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 4. After the SiC deposition was completed, the TaC layer was deposited at a deposition temperature of 1200° C. and a deposition pressure of 4500 Pa. The reaction system was tantalum pentachloride / propylene / hydrogen / argon, and the deposition time was 6 h. The tantalum pentachloride feed rate was 280 r / min, and the hydrogen / propylene ratio was 7.5.
[0027] The BN layer (3 μm) was prepared by chemical vapor deposition, with a deposition temperature of 600° C., a reaction pressure of 4000 Pa, a deposition time of 2 h, and a reaction system of boron trichloride / ammonia / nitrogen / hydrogen / argon, wherein the ratio of boron trichloride / ammonia / nitrogen / hydrogen was 1:3:6:1;
[0028] The aluminum oxide coating (2 μm) was prepared by chemical vapor deposition, with a deposition temperature of 1000 °C, a deposition pressure of 30 kPa, and a reaction gas of gaseous aluminum halide;
[0029] Ti a B b The coating (3 μm) was prepared by chemical vapor deposition with a deposition temperature of 700°C and a preparation pressure of 3000 Pa. BCl3 was used as the boron source of the coating, TiCl4 was used as the titanium source of the coating, and H2 was used as the carrier gas; the ratio of BCl3, TiCl4 and H2 was 1:4:5.
[0030] Example 2
[0031] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0032] The SiC-TaC layer (4 μm) was prepared by chemical vapor deposition. First, SiC was deposited at a deposition temperature of 1250°C and a deposition pressure of 1000 Pa. The reaction system was trichloromethylsilane / hydrogen / argon. The total deposition time was 7 h, which was divided into three stages. The deposition time of the first stage was 3 h, and the hydrogen / trichloromethylsilane ratio was 2. The deposition time of the second stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 3. The deposition time of the third stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 4. After the SiC deposition was completed, the TaC layer was deposited at a deposition temperature of 1300°C and a deposition pressure of 5000 Pa. The reaction system was tantalum pentachloride / propylene / hydrogen / argon, and the deposition time was 6 h. The tantalum pentachloride feed rate was 280 r / min, and the hydrogen / propylene ratio was 7.5.
[0033] The BN layer (4 μm) was prepared by chemical vapor deposition, with a deposition temperature of 600-700° C., a reaction pressure of 4000-5000 Pa, a deposition time of 2 h, and a reaction system of boron trichloride / ammonia / nitrogen / hydrogen / argon, wherein the ratio of boron trichloride / ammonia / nitrogen / hydrogen was 1:3:6:1;
[0034] The aluminum oxide coating (3 μm) was prepared by chemical vapor deposition, with a deposition temperature of 1050 °C, a deposition pressure of 35 kPa, and a reaction gas of gaseous aluminum halide;
[0035] Ti a B b The coating (4 μm) was prepared by chemical vapor deposition with a deposition temperature of 800°C and a preparation pressure of 4000 Pa. BCl3 was used as the boron source of the coating, TiCl4 was used as the titanium source of the coating, and H2 was used as the carrier gas; the ratio of BCl3, TiCl4 and H2 was 1:4:5.
[0036] Example 3
[0037] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0038] The SiC-TaC layer (6 μm) was prepared by chemical vapor deposition. First, SiC was deposited at a deposition temperature of 1300° C. and a deposition pressure of 1100 Pa. The reaction system was trichloromethylsilane / hydrogen / argon. The total deposition time was 7 h, which was divided into three stages. The deposition time of the first stage was 3 h, and the hydrogen / trichloromethylsilane ratio was 2. The deposition time of the second stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 3. The deposition time of the third stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 4. After the SiC deposition was completed, the TaC layer was deposited at a deposition temperature of 1400° C. and a deposition pressure of 5500 Pa. The reaction system was tantalum pentachloride / propylene / hydrogen / argon, and the deposition time was 6 h. The tantalum pentachloride feed rate was 280 r / min, and the hydrogen / propylene ratio was 7.5.
[0039] The BN layer (5 μm) was prepared by chemical vapor deposition, with a deposition temperature of 700° C., a reaction pressure of 5000 Pa, a deposition time of 2 h, and a reaction system of boron trichloride / ammonia / nitrogen / hydrogen / argon, wherein the ratio of boron trichloride / ammonia / nitrogen / hydrogen was 1:3:6:1;
[0040] The aluminum oxide coating (4 μm) was prepared by chemical vapor deposition, with a deposition temperature of 1100 °C, a deposition pressure of 40 kPa, and a reaction gas of gaseous aluminum halide;
[0041] Ti a B bThe coating (5 μm) was prepared by chemical vapor deposition method with a deposition temperature of 900°C and a preparation pressure of 5000 Pa. BCl3 was used as the boron source of the coating, TiCl4 was used as the titanium source of the coating, and H2 was used as the carrier gas; the ratio of BCl3, TiCl4 and H2 was 1:4:5.
[0042] Example 4
[0043] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0044] The BN layer (4 μm) was prepared by chemical vapor deposition, with a deposition temperature of 600-700° C., a reaction pressure of 4000-5000 Pa, a deposition time of 2 h, and a reaction system of boron trichloride / ammonia / nitrogen / hydrogen / argon, wherein the ratio of boron trichloride / ammonia / nitrogen / hydrogen was 1:3:6:1;
[0045] The aluminum oxide coating (3 μm) was prepared by chemical vapor deposition, with a deposition temperature of 1050 °C, a deposition pressure of 35 kPa, and a reaction gas of gaseous aluminum halide;
[0046] Ti a B b The coating (4 μm) was prepared by chemical vapor deposition with a deposition temperature of 800°C and a preparation pressure of 4000 Pa. BCl3 was used as the boron source of the coating, TiCl4 was used as the titanium source of the coating, and H2 was used as the carrier gas; the ratio of BCl3, TiCl4 and H2 was 1:4:5.
[0047] Example 5
[0048] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0049] The SiC-TaC layer (4 μm) was prepared by chemical vapor deposition. First, SiC was deposited at a deposition temperature of 1250°C and a deposition pressure of 1000 Pa. The reaction system was trichloromethylsilane / hydrogen / argon. The total deposition time was 7 h, which was divided into three stages. The deposition time of the first stage was 3 h, and the hydrogen / trichloromethylsilane ratio was 2. The deposition time of the second stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 3. The deposition time of the third stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 4. After the SiC deposition was completed, the TaC layer was deposited at a deposition temperature of 1300°C and a deposition pressure of 5000 Pa. The reaction system was tantalum pentachloride / propylene / hydrogen / argon, and the deposition time was 6 h. The tantalum pentachloride feed rate was 280 r / min, and the hydrogen / propylene ratio was 7.5.
[0050] The aluminum oxide coating (3 μm) was prepared by chemical vapor deposition, with a deposition temperature of 1050 °C, a deposition pressure of 35 kPa, and a reaction gas of gaseous aluminum halide;
[0051] Ti a B b The coating (4 μm) was prepared by chemical vapor deposition with a deposition temperature of 800°C and a preparation pressure of 4000 Pa. BCl3 was used as the boron source of the coating, TiCl4 was used as the titanium source of the coating, and H2 was used as the carrier gas; the ratio of BCl3, TiCl4 and H2 was 1:4:5.
[0052] Example 7
[0053] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0054] The SiC-TaC layer (4 μm) was prepared by chemical vapor deposition. First, SiC was deposited at a deposition temperature of 1250°C and a deposition pressure of 1000 Pa. The reaction system was trichloromethylsilane / hydrogen / argon. The total deposition time was 7 h, which was divided into three stages. The deposition time of the first stage was 3 h, and the hydrogen / trichloromethylsilane ratio was 2. The deposition time of the second stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 3. The deposition time of the third stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 4. After the SiC deposition was completed, the TaC layer was deposited at a deposition temperature of 1300°C and a deposition pressure of 5000 Pa. The reaction system was tantalum pentachloride / propylene / hydrogen / argon, and the deposition time was 6 h. The tantalum pentachloride feed rate was 280 r / min, and the hydrogen / propylene ratio was 7.5.
[0055] The BN layer (4 μm) was prepared by chemical vapor deposition, with a deposition temperature of 600-700° C., a reaction pressure of 4000-5000 Pa, a deposition time of 2 h, and a reaction system of boron trichloride / ammonia / nitrogen / hydrogen / argon, wherein the ratio of boron trichloride / ammonia / nitrogen / hydrogen was 1:3:6:1;
[0056] Ti a B b The coating (4 μm) was prepared by chemical vapor deposition with a deposition temperature of 800°C and a preparation pressure of 4000 Pa. BCl3 was used as the boron source of the coating, TiCl4 was used as the titanium source of the coating, and H2 was used as the carrier gas; the ratio of BCl3, TiCl4 and H2 was 1:4:5.
[0057] Example 8
[0058] The CVD coating is sequentially deposited on the surface of the microporous wire drawing die substrate, and the preparation method is as follows:
[0059] The SiC-TaC layer (4 μm) was prepared by chemical vapor deposition. First, SiC was deposited at a deposition temperature of 1250°C and a deposition pressure of 1000 Pa. The reaction system was trichloromethylsilane / hydrogen / argon. The total deposition time was 7 h, which was divided into three stages. The deposition time of the first stage was 3 h, and the hydrogen / trichloromethylsilane ratio was 2. The deposition time of the second stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 3. The deposition time of the third stage was 2 h, and the hydrogen / trichloromethylsilane ratio was 4. After the SiC deposition was completed, the TaC layer was deposited at a deposition temperature of 1300°C and a deposition pressure of 5000 Pa. The reaction system was tantalum pentachloride / propylene / hydrogen / argon, and the deposition time was 6 h. The tantalum pentachloride feed rate was 280 r / min, and the hydrogen / propylene ratio was 7.5.
[0060] The BN layer (4 μm) was prepared by chemical vapor deposition, with a deposition temperature of 600-700° C., a reaction pressure of 4000-5000 Pa, a deposition time of 2 h, and a reaction system of boron trichloride / ammonia / nitrogen / hydrogen / argon, wherein the ratio of boron trichloride / ammonia / nitrogen / hydrogen was 1:3:6:1;
[0061] The aluminum oxide coating (3 μm) was prepared by chemical vapor deposition with a deposition temperature of 1050° C., a deposition pressure of 35 kPa, and a reaction gas of gaseous aluminum halide.
[0062] Test Example 1
[0063] The film-substrate bonding strength, anti-oxidation temperature, hardness and friction coefficient of each CVD coating in Examples 1 to 8 are shown in Table 1.
[0064] Table 1 Test results
[0065]
[0066] From the experimental data table provided, we can see that the CVD coatings of Examples 1 to 3 all exhibit good performance in terms of film-substrate bonding, oxidation resistance temperature, hardness, friction coefficient, etc. However, in other examples, there are some factors that lead to performance degradation.
[0067] In particular, the film-to-substrate bonding strength of Example 4 is relatively low, which is attributed to the fact that it is not tightly bonded to the substrate contact layer during the deposition process. Although the specific material layer is mentioned as the BN layer here, for the purpose of desensitization, we can generalize it as a "specific contact layer" to avoid directly revealing the specific material information.
[0068] For Examples 5 and 6, although their film-substrate bonding strength is good, due to the Ti a B bThere is only one layer of separation between the coating and the substrate, which makes the coating unable to effectively block the diffusion of certain elements on the substrate surface (generalized as "X phase" here). This diffusion limits the Ti a B b The deposition effect affects the overall performance of the coating.
[0069] Finally, in Example 7, since Ti was not deposited in the end a B b , resulting in a significant decrease in the hardness of the coating.
[0070] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A CVD coated microporous wire drawing die for cemented carbide, characterized in that: The microporous wire drawing die substrate is made of WC-8% Co hard alloy, and the CVD coating is SiC-TaC layer / BN layer / aluminum oxide coating / Ti from the surface of the microporous wire drawing die substrate to the outside. a B b coating.
2. The CVD coated microporous wire drawing die for cemented carbide according to claim 1, characterized in that: The total thickness of the CVD coating is 10-20 μm, wherein the SiC-TaC layer (2-6 μm) / BN layer (3-5 μm) / aluminum oxide coating (2-4 μm) / Ti a B b Coating (3-5 μm).
3. The CVD coated microporous wire drawing die for cemented carbide according to claim 1, characterized in that: The SiC-TaC layer is prepared by a chemical vapor deposition method. First, SiC is deposited at a deposition temperature of 1200-1300° C., a deposition pressure of 900-1100 Pa, a reaction system of trichloromethylsilane / hydrogen / argon, a total deposition time of 7 hours, and the method is divided into three stages. The deposition time of the first stage is 3 hours, and the hydrogen / trichloromethylsilane is 2; the deposition time of the second stage is 2 hours, and the hydrogen / trichloromethylsilane is 3; the deposition time of the third stage is 2 hours, and the hydrogen / trichloromethylsilane is 4; after the SiC deposition is completed, a TaC layer is deposited at a deposition temperature of 1200-1400° C., a deposition pressure of 4500-5500 Pa, a reaction system of tantalum pentachloride / propylene / hydrogen / argon, and a deposition time of 6 hours.
4. The CVD coated micro-hole wire drawing die for cemented carbide according to claim 3, characterized in that: The purity of the tantalum pentachloride is greater than 99.95%.
5. The CVD coated micro-hole wire drawing die for cemented carbide according to claim 3, characterized in that: The feeding rate of the tantalum pentachloride is 280 r / min.
6. The CVD coated micro-hole wire drawing die for cemented carbide according to claim 3, characterized in that: The hydrogen / propylene ratio is 7.
5.
7. The CVD coated micro-hole wire drawing die for cemented carbide according to claim 1, characterized in that: The BN layer is prepared by chemical vapor deposition, the deposition temperature is 600-700° C., the reaction pressure is 4000-5000 Pa, the deposition time is 2 hours, the reaction system is boron trichloride / ammonia / nitrogen / hydrogen / argon, and the boron trichloride / ammonia / nitrogen / hydrogen is 1:3:6:
1.
8. The CVD coated micro-hole wire drawing die for cemented carbide according to claim 1, characterized in that: The aluminum oxide layer is prepared by chemical vapor deposition, the deposition temperature is 1000-1100° C., the deposition pressure is 30-40 kPa, and the reaction gas is gaseous aluminum halide.
9. The CVD coated micro-hole wire drawing die suitable for cemented carbide according to claim 1, characterized in that: The Ti a B b The coating is prepared by chemical vapor deposition method, the deposition temperature is 700-900°C, the preparation pressure is 3000-5000Pa, BCl3 is used as the boron source of the coating, TiCl4 is used as the titanium source of the coating, and H2 is used as the carrier gas.
10. The CVD coated micro-hole wire drawing die suitable for cemented carbide according to claim 8, characterized in that: The BCl3, TiCl4 and H2 are in the ratio of 1:4:5.